No Need to Watch: How the Effects of Partisan Media Can Spread via Interpersonal Discussions. Issue 1 (8th August 2017) - Druckman, James N.; Levendusky, Matthew S.; McLain, Audrey
Abstract: To what extent do partisan media sources shape public opinion? On its face, it would appear that the impact of partisan media is limited, given that it attracts a relatively small audience. We argue, however, that its influence may extend beyond its direct audience via a two‐step communication flow. Specifically, those who watch and are impacted by partisan media outlets talk to and persuade others who did not watch. We present experimental results that demonstrate this process. We therefore show that previous studies may have significantly underestimated the effect of these outlets. We also illustrate that how the two‐step communication flow works is contingent upon the precise composition of the discussion group (e.g., is it consistent of all fellow partisans or a mix of partisans?). We conclude by highlighting what our results imply about the study of media, preference formation, and partisan polarization.